Creating a Sustainable and Supportive Teaching Practicum in Rural and Regional Locations - Ryan, Josephine; Jone, Melitta (Australian and International Journal of Rural Education, 2012)
The study described in this paper creating an effective practicum model for rural and regional preservice teachers is designed to address the ongoing difficulties experienced by schools and universities as they seek to provide high quality preservice teacher education for individuals in rural areas. Lecturers from the regional campuses of two Australian universities have jointly undertaken a study of various initiatives designed to improve the way they manage the rural teaching practicum. The study also investigates the perspectives of rural and regional teachers about how they can best be supported by universities in their supervision of preservice teachers. The findings reveal the potential of two under-utilised approaches to the rural and regional practicum: the use of inter-university partnerships and technology to improve support and learning for preservice teachers in rural and regional locations.